(3CMcGe GdehGdjOs - (3CHh Ydj jMji Hf ZGdH Hf eMeO GdHZOGOj GdNjGW,J (B220 (3g` s
(3ChdgG (B:s
(3GdHGH GdChd eG jMJGL Edjg ai Yde GdehGdjO bGd (B: (3aChd eG jMJGL Edjg ai Yde GdehGdjO ai Yde GdJQHjI heYQaJgG hGdSHjd ai Pdc Cf jfXQ Edi CQHGH eKdKGJ GdWGdY s
(3BNQgG (B:s
(3aGJNPg OdjdkG ddLPH GdZGdH Ydi OQLI GdELJeGY , hGLYd OQLI GdhJO GdbQjHI efg eKd OQL GdchcH , hCbe HGbi HjhJ Gdadc ef GdMSGH Je s
(3Vef eLehY s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B162 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B109 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B516s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B250 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B394 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3Gdadcs